Advanced cocaine-related necrotising sinusitis presenting with restrictive ophthalmolplegia. (3rd May 2016) - Lascaratos, Gerassimos; McHugh, James; McCarthy, Karon; Bunting, Howard
ABSTRACT: We report a case of bilateral infero-medial orbital wall destruction, associated with loss of sinonasal architecture. The patient presented with intermittent horizontal diplopia following an acute on chronic infective sinusitis. Eight months previously the patient had developed a midline hard palate fistula for which a palatine prosthesis had been fitted. The broad differential diagnosis is discussed, though in this patient chronic cocaine abuse was identified as the underlying aetiology. Eye movement restriction worsened progressively with bilateral inflammation around the medial and inferior rectus muscles. Attempts to resolve the recurring cycle of sinus infection and inflammation by palatal fistula closure failed despite augmented techniques mobilising flaps from both nasal and palatal sides.